“People Aren’t Afraid Anymore, But It’s Hard to Find Books": Reading Practices That Inform the Personal and Social Identities of Self-Identified Lesbian and Queer Young Women - Rothbauer, Paulette M. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
This presentation is an overview of findings from my dissertation research into the voluntary reading practices of lesbian and queer young women. Three themes emerged from analysis of in-depth interviews: reading as escape, reading for possibilities, and reading for community. The roles of libraries, bookstores and the Internet are discussed. Cette présentation donne un aperçu des résultats de mon mémoire de recherche sur les pratiques volontaires de lecture de lesbiennes et de jeunes femmes allosexuelles. Trois thèmes découlent de cette analyse d’entrevues en profondeur : la lecture comme évasion, la lecture comme potentiel et la lecture pour la collectivité. Le rôle des bibliothèques, des librairies et d’Internet est examiné.